Communicative skin: marginalization, transformative identity and forced tattoo narratives in Joyce Carol Oates’ The Tattooed Girl - Biswas, Antara; Gaur, Rashmi (Penerbit Universiti Kebangsaan Malaysia, 2025)
Discourses on tattoos often emphasize self-assertion and individual expression. However, the phenomenon of “forced tattooing”—the imposition of tattoos without the tattooee’s deliberate consent—often remains overlooked despite its role in communicating complex narratives to those who behold them (Osterud, 2014, p. 56). This article investigates the novel The Tattooed Girl (2006) by Joyce Carol Oates, examining the untapped role of forced tattoos to unravel the transformative narrative of a marginalized woman. Drawing upon Mary Kosut’s (2000) theory of tattoo narratives, the present study argues that Oates’ protagonist Alma Busch’s involuntarily inscribed tattoos function as non-verbal communicative channels, narrating her journey of self-reclamation from a doubly marginalized and submissive self. By examining the non-verbal and interpretive dimensions of Alma’s tattoos, this article offers a new lens on forced tattoos as strategic narratives of silence, resilience, and transformative potential in literature, thus contributing to feminist discussions on body inscriptions as expressions of agency and reconfiguration. The article, therefore, invites a further scope on the intersection of body inscriptions, memory, ethics and culture as a potential area for future research in literary studies and beyond.